2000
DOI: 10.1093/fampra/17.suppl_2.s6
|View full text |Cite
|
Sign up to set email alerts
|

The management of Helicobacter pylori infection in primary care: a systematic review of the literature

Abstract: Childs SM, Roberts AP, Meineche-Schmidt V, de Wit NJ and Rubin GP. The management of Helicobacter pylori infection in primary care: a systematic review of the literature. Family Practice 2000; 17: S6-S11. Objective. The aim of the present study was to provide evidence from the literature to inform the production of guidelines by the European Society for Primary Care Gastroenterology (ESPCG) for the management of Helicobacter pylori infection in primary care. Methods. A systematic review was conducted, searchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Of 84 potentially relevant citations, 47 studies were identified as systematic reviews from their abstracts 2,3,6,8–51 . However, subsequent scrutiny of the full articles excluded eight studies that did not meet the criteria for meta‐analysis either because they did not show statistical synthesis of results from the primary studies 13,16,41,47–51 or, as in one study, duplicate publication 35 . Therefore, the current critical appraisal included 38 studies 2,3,6,8–12,14,15,17–34,36–40,42–46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 84 potentially relevant citations, 47 studies were identified as systematic reviews from their abstracts 2,3,6,8–51 . However, subsequent scrutiny of the full articles excluded eight studies that did not meet the criteria for meta‐analysis either because they did not show statistical synthesis of results from the primary studies 13,16,41,47–51 or, as in one study, duplicate publication 35 . Therefore, the current critical appraisal included 38 studies 2,3,6,8–12,14,15,17–34,36–40,42–46 …”
Section: Resultsmentioning
confidence: 99%
“…Helicobacter pylori infection is highly prevalent, occurring in approximately 50% of the world's adult population, 5 and is associated with a number of upper gastrointestinal diseases 6–8 . In the past 16 years, a large number of epidemiological studies and clinical trials dealing with this infection have been published and subsequently meta‐analyzed to produce summary estimates of risk in the causal relationship between infection and disease or efficacy of different treatment strategies 2,3,6,8–51 . The aim of the current critique is to review the methodological strengths and weaknesses of these meta‐analyses, particularly with respect to the assessment and handling of heterogeneity.…”
Section: Introductionmentioning
confidence: 99%